Concussion in the National Hockey League: a systematic review of the literature - Kuhn, A. W.; Solomon, G. S. (Concussion, 2015)
Players in the National Hockey League (NHL) are often sidelined by injuries, including concussion. The acute, intermediate and long-term effects of repetitive head trauma remain a concern of many. In 1997, the NHL and NHL Players Association established the NHL-NHL Players Association Concussion Program to diagnose, assess and treat concussion via a standardized and scientific approach. Documenting and analyzing the trends, incidence and underlying mechanisms of concussion may help in devising future prevention and treatment plans for concussion in hockey in general and the NHL in particular. The purpose of this study, therefore, was to systematically review and summarize the existing published literature on the trends, incidence rates and underlying mechanisms of concussion in the NHL.